2009
DOI: 10.1161/circresaha.108.184408
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase G Modulates Human Myocardial Passive Stiffness by Phosphorylation of the Titin Springs

Abstract: Abstract-The sarcomeric titin springs influence myocardial distensibility and passive stiffness. Titin isoform composition and protein kinase (PK)A-dependent titin phosphorylation are variables contributing to diastolic heart function. However, diastolic tone, relaxation speed, and left ventricular extensibility are also altered by PKG activation. We used back-phosphorylation assays to determine whether PKG can phosphorylate titin and affect titin-based stiffness in skinned myofibers and isolated myofibrils. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
275
1
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 358 publications
(293 citation statements)
references
References 40 publications
10
275
1
7
Order By: Relevance
“…This finding could be attributed to decreased phosphorylation of the large elastic cytoskeletal protein titin. Phosphorylation of titin by PKG decreases passive stiffness in cardiac myofibrils, and recent evidence has shown that increased passive stiffness in isolated cardiomyocytes from human HFpEF patients is associated with reduced cGMP levels and subsequent PKG activity 7, 8, 9. Contrary to these findings, cGMP levels and PKG activity were unaltered in the HF group of the current study compared to CON.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…This finding could be attributed to decreased phosphorylation of the large elastic cytoskeletal protein titin. Phosphorylation of titin by PKG decreases passive stiffness in cardiac myofibrils, and recent evidence has shown that increased passive stiffness in isolated cardiomyocytes from human HFpEF patients is associated with reduced cGMP levels and subsequent PKG activity 7, 8, 9. Contrary to these findings, cGMP levels and PKG activity were unaltered in the HF group of the current study compared to CON.…”
Section: Discussioncontrasting
confidence: 90%
“…Cyclic guanosine monophosphate (cGMP) levels modulate many signaling pathways regulating diastolic function and may inhibit ventricular hypertrophy and stiffness while promoting diastolic relaxation 5, 6, 7, 8. There is growing evidence the cGMP signaling cascade is disturbed in HFpEF patients and could contribute to diastolic dysfunction 4, 5, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence indicates that FHL1 functions in the hypertrophic biomechanical stress response (31) and that FHL2 functions in localizing various metabolic enzymes (32). In addition, the N2B-Us contains sequences that can be phosphorylated by PKA (34) and PKG (35) and that thereby tune the compliance of the N2B-Us spring. It is likely that these important N2B-Us functions (binding FHL1/2, responding to phoshorylation) depend on local secondary structures and that ␣B-crystallin is required to maintain these structures, especially when the heart is stressed, such as during ischemia (29).…”
Section: ␣B-crystallinmentioning
confidence: 99%
“…Titin properties can also be modulated in short term by post-translational modification of the elastic I-band domains N2-B unique sequence (N2-Bus) and PEVK (titin domain rich in proline, glutamate, valine, and lysine). Phosphorylation within the cardiac-specific N2-Bus by cAMP-dependent protein kinase, cGMP-dependent protein kinase, extracellular signal-regulated kinase 1/2 (Erk1/2), and Ca 2+ /calmodulin-dependent protein kinase II delta (CaMKIIδ) decreases titin-based cardiac myocyte stiffness, [13][14][15][16][17][18] whereas phosphorylation of the PEVK domain by Ca…”
mentioning
confidence: 99%